“They Knew How to Respect Children”: Life Histories and Culturally Appropriate Education - Leavitt, Robert (Canadian Journal of Education/Revue canadienne de l'éducation, 1994)
Nkisi wolosakihtunol kisuwikhomuhticil 'tatkuhkakonol Wolastoqihik naka Mihkomak, etoli spokehkitimok Sitansisk. Nkissakihtunol ona 'tatkuhkakonuwal 'ceyak elomahkiwik sawonehsonuk, etolokehkimsulticik. Psi te yukt nutuwikhikhoticik moskomoniya ansa te tan op wen oli aqami kisi skicinuwokehkiman. Yut itomuwiw, yatte wen atkuhkalsu, menakaci tpitahasu, aptuwikhiket. Yut ona toke nit ollukhotimk, nutokehkimut oc 'komasi wicuhkema, aqamihc ona nonasu, peyemi nonom, naka woli kcicihtuwan wetapeksit. (Maliseet-Passamaquoddy translation by David A. Francis) In this article I examine educational biographies and autobiographies by Canadian Maliseet and Micmac university students and by Bolivian Aymara, Quechua, and Uru women engaged in self-education. There writers have discovered something about learning that teachers will find useful in designing culturally appropriate education: that is, that collective work and reflection help define the individual within her culture and her community. Knowing this, teachers can use student collaboration and independent work to help students expand their knowledge and understanding of themselves and of their own culture. Cet article étudie les biographies et autobiographies d’étudiants universitaires malécites et micmacs ainsi que de Boliviennes aymaras, quechuas et urus pratiquant l’autodidaxie. Ces auteurs ont découvert, au sujet de l’apprentissage, un principe que les enseignants pourront mettre à profit lorsqu’ils auront à concevoir des cours offrant une pertinence culturelle, à savoir que le travail et la réflexion en commun aident à définir l’individu au sein de sa culture et de sa communauté. Sachant cela, les enseignants peuvent faire appel à la collaboration de leurs élèves et à leur initiative personnelle pour les aider à parfaire leurs connaissances et à mieux se comprendre eux-mêmes ainsi que leur culture.